Maternal intra‐ and postpartum near‐miss following assisted reproductive technology: a retrospective study. (10th July 2018) - Cromi, A; Marconi, N; Casarin, J; Cominotti, S; Pinelli, C; Riccardi, M; Ghezzi, F
Abstract : Objective: To assess whether risk of severe maternal morbidity at delivery differs for women who conceived using assisted reproductive technology (ART), compared with those with a spontaneous conception. Design: A cohort study using a prospectively maintained institutional database. Setting: A tertiary university maternity hospital. Population: All women delivering at Del Ponte Hospital, Italy, between 2005 and 2016. Methods: Data from 650 ART‐conceived pregnancies were compared with 22 803 spontaneously conceived pregnancies. We used multivariable analysis to estimate the odds of severe maternal morbidity at delivery associated with ART conception, adjusting for maternal demographic and health factors, gestational age, and mode of delivery. Main outcome measures: The World Health Organization criteria for potentially life‐threatening conditions and near‐miss maternal mortality were used. Results: The incidence of near‐miss in the entire cohort was 3.3 cases per 1000 births (95% confidence interval, 95% CI, 2.6–4.1). The crude prevalences of potentially life‐threatening conditions and maternal near‐miss were higher among ART than among non‐ART deliveries (27.1 versus 5.7% and 2.6 versus 0.3%, respectively). The three most common causes of maternal near‐miss cases were peripartum hysterectomy, transfusion of ≥5 units of red blood cells, and cardiovascular dysfunction requiring vasoactive drugs. The odds of a maternal near‐miss at delivery were increased for ART‐conceived pregnancies compared with non‐ART‐conceived pregnancies (adjusted odds ratio, aOR 3.61, 95% CI 1.61–8.09, for ART‐conceived pregnancies with autologous oocytes; aOR 13.57, 95% CI 5.45–33.77, for ART pregnancies conceived with donor oocytes). Conclusion: Although we cannot exclude unmeasured confounding, we found that pregnancies conceived via ART, especially those conceived with donor oocytes, are at increased risk of maternal potentially life‐threatening conditions and near‐miss at delivery. Funding: This research received no specific grant from any funding agency in the public, commercial, or not‐for‐profit sectors. Tweetable abstract: Conceiving through assisted reproductive technology increases the likelihood of maternal near miss. Tweetable abstract: Conceiving through assisted reproductive technology increases the likelihood of maternal near miss.